A COMPARATIVE ANALYSIS OF WRITING SKILLS IN MEITEILON (L1) AND ENGLISH (L2) AMONG HIGHER SECONDARY STUDENTS IN MANIPUR - Chenglei, Wairokpam Yaiphaba (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There has always been discussion among academics, policymakers, and educators over the impact of mother tongue, or first language (L1), on second language (L2) acquisition or learning. Reaching a level of competence similar to that of a native speaker is the aim of teaching second language. Almost all Indian languages are structured in a subject-object-verb (SOV) pattern, while English uses a subject-verb-object (SVO) patter. Further, many English words of the same spelling perform different parts of speech with different meanings. As a result of this confusion, it remains a big challenge for learners of English as a second language in written skills. Writing skills improve our ability to communicate and think. It also improves our capacity to clarify and improve our concepts for both ourselves and other people. Writing abilities are crucial for effective communication. Whether a mother tongue can help, fails to help, or actually impedes written communication skills in English has been the subject of extensive research. The present paper is making an attempt to analyse the writing skills of Meiteilon (L1) and English language (L2).